GAAS تأثير استخدام الحاسوب في عمل نظم المعلومات المحاسبية على معايير التدقيق المقبولة قبولا عاما - د. زياد هاشم السقا; د. صالح ابراهيم الشعباني; د. ناظم حسن الطائي (PROSPECTIVE RESEARCHES, 2023)
The present research tackles an important topic in the field of control (checking) which concerns studying control parameters generally accepted. We try to evaluate these parameters and promote them to cope with the new needs using the computer to form accounting database. The research falls into four sections. Section one tackles the nature of generally accepted control parameters. Section two shows the effects of using computers in the work of accounting database on the personal parameters. Section three displays the effect of using computers in the work of accounting database on the parameters of fieldwork. Finally, section four presents the effect of computers in the work of accounting database on the parameters of giving opinions "the report". The research has come up with a set of useful conclusions.